Max Einstein : Rebels With a Cause - Patterson, James 1947-; Grabenstein, Chris; Johnson, Beverly (New York ; JIMMY Patterson Books, Little Brown and Company, 2019)
When twelve-year-old Max's friend Vihaan asks her help for a village in India with a water crisis, Max risks her safety to try to save the day.
Keywords: Adventure and adventurers -- Fiction; Water -- Fiction -- Pollution; Science -- Fiction -- Experiments; Problem solving -- Fiction; Creative ability -- Fiction; Genius -- Fiction; India -- Fiction